The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bbrep.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Trim33 regulates early maturation of mouse embryoid bodies in vitro

Abstract: Embryonic stem cells (ESCs) are an established model for investigating developmental processes, disease conditions, tissue regeneration and therapeutic targets. Previous studies have shown that tripartite motif-containing 33 protein (Trim33) functions as a chromatin reader during Nodal-induced mesoderm induction. Here we report that despite reduced proliferation, mouse ESCs deficient in Trim33 remained pluripotent when cultured under non-differentiating conditions. However, when induced to differentiate to emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Previously, the engagement of TRIM33 protein in the regulation of stem cell phenotype has been presented in a normal embryonic stem cell population [ 35 , 36 ]. In contrast to TRIM24 and TRIM28, TRIM33 seems to be a positive regulator of stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the engagement of TRIM33 protein in the regulation of stem cell phenotype has been presented in a normal embryonic stem cell population [ 35 , 36 ]. In contrast to TRIM24 and TRIM28, TRIM33 seems to be a positive regulator of stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the other TIF1 family members, TRIM33 has predominantly been identified as a tumor suppressor [ 29 , 30 , 31 , 32 ], although several studies imply its engagement in promoting cancer progression [ 33 , 34 ]. It was previously demonstrated that TRIM33 downregulation does not affect stem cell maintenance, but instead, it alters the cell differentiation process [ 35 , 36 ]. As for TRIM66, its role in cancer progression still remains largely unknown, although a few studies suggest that TRIM66 acts as an oncogene [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptional intermediary factor 1 γ (TIF1γ), synonymous with TRIM33, RFG7, PTC7, or Ectodermin, is an E3 ubiquitin-ligase family member with a ring-box-coiled-coil region (1). It has been reported to play a role in transcription elongation (2, 3), DNA repair (4), differentiation of cells (2, 5, 6), embryonic development (69), mitosis (10), and dermatomyositis (1113). As transforming growth factor-β (TGF-β) superfamily signaling plays an important role in the occurrence and development of cancer (1416), and TIF1γ was reported to be involved in the regulation of TGF-β superfamily signaling (17, 18), recent studies on TIF1γ have focused on its role in tumorigenesis (10, 1924).…”
Section: Introductionmentioning
confidence: 99%